Performance by design : the systematic selection, design, and development of performance technologies that produce useful results - Watkins, Ryan (HPT in action series ;, 2007)
At the end of the day, our jobs are all about results. The desire to achieve useful results should guide your decisions on a daily basis. This book & rsquo;s unique Performance by Design approach and framework will systematically walk you through the processes, procedures, tools and techniques that are most valuable in creating performance systems that achieve results. In eight chapters, the book sequentially describes each step in the Performance by Design framework: What is performance; Identify desired performance; Define success; Define performance assessments; Identify a set of solutions; D.